The oral health impact profile and well-being on mothers and preschool children - Bianca Núbia Souza Silva; Lucas Arrais de Campos; João Maroco; Juliana Alvares Duarte Bonini Campos (BMC, 2024)
Abstract Objectives to verify the contribution of mothers' oral health impact profile to their children's oral health profile and the contribution of mothers' well-being and the caries index (dmft) to children's well-being. Methods This is a cross-sectional observational study. Mothers and pre-school children enrolled in public schools in the municipality of Araraquara-SP took part. The Oral Health Impact Profile Questionnaire (OHIP-14), Satisfaction with Life Scale (SWLS), Early Childhood Oral Health Impact Scale (ECOHIS) and the Autoquestionnaire Qualité de Vie Enfant Imagé (AUQEI) were used. To diagnose caries, a clinical examination was carried out to calculate the dmft index. Path analysis was carried out and the path coefficients were estimated (β) and evaluated using the z-test (α = 5%). Results 443 children took part (5.19 ± 0.64 years; 52.4% boys) with an mean dmft of 1.31 ± 2.19. The mean age of the mothers was 33.4 ± 7.01 years. There was a significant impact of dmft and maternal well-being on the child's subjective well-being (s2explained = 43%). The mothers' oral health impact profile and the child's caries experience had a significant influence on both the child (OHIP: β = 0.22; p < 0.001; dmft: β = 0.48; p < 0.001) and the family (OHIP: β = 0.29; p < 0.001; dmft: β = 0.32; p < 0.001). The child's dmft (β=-0.10; p = 0.005) and the mothers' subjective well-being (β=-0.61; p < 0.001) had a significant impact on the child's subjective well-being. Conclusion The mothers' oral health impact profile and the child's caries experience had an impact on both the child and the family. Mothers' subjective well-being and caries experience should be considered when assessing the subjective well-being of Brazilian preschool children.